Relationship between soil temperature and soil degree days with pod yield of groundnut (Arachis hypogaea) as influenced by different mulches and land configurations - SUBRAHMANIYAN, K; PARTHIPAN, T; VEERAMANI, P; MAHALINGAM, A; SANGEETHA, A (The Indian Journal of Agricultural Sciences, 2025)
This study was carried out during rainy (kharif) season of 2020–2023 at Tamil Nadu Rice Research Institute (Tamil Nadu Agricultural University, Coimbatore), Aduthurai, Tamil Nadu to study the functional relationship between soil thermal indices and crop growth parameters and yield of groundnut (Arachis hypogaea L.) under different mulches and land configurations. Field experiment was conducted during south-west monsoon (SWM) with three mulches, viz. No mulch (NM), Organic mulch (OM) and Polyethylene film mulch (PMG) and four land configurations, viz. Flatbed (FB), Broad bed furrow (BBF), Ridges and furrows (RF) and Raised bed and furrow (RBF). The 4-year pooled results indicated that soil temperatures were significantly higher under polyethylene film mulched groundnut in different phenophases from sowing to harvest compared to non-mulch and organic mulches. Similarly, the soil degree- days (SDD) varied significantly among the different mulches and the total accumulated soil degree days in different phenophases were highest with transparent film mulch. The increase in the accumulated soil degree days shortened the crop period and the crop attained maturity six days earlier than no mulch and organic mulch. The soil temperature and soil degree days were lower with organic mulch as compared to no mulch. The coefficient of determination (R2) at three depths ranged from a value of 0.991–0.996 for pod yield and soil temperature which indicated a strong correlation. The soil warming efficiency of land configurations was in the order of ridges and furrows>raised bed>broad bed and furrow>flat bed. Due to an increase in the growth and yield attributes, the pod yield obtained with transparent plastic mulch was 16.48% higher than the non-mulched control. The raised bed and furrow method of land configuration produced a higher yield of 2500 kg/ha, which was 13.17 % higher than the broad bed and furrow.